THE EFFECT OF NON-FINANCIAL PERFORMANCE WITH ADDITIONAL ENVIRONMENTAL PERFORMANCE ON FINANCIAL PERFORMANCE ON PERFORMANCE EVALUATION BASED ON THE BALANCED SCORECARD (BSC) WITH MANAGEMENT COMMUNICATION AS MODERATING VARIABLE - Dian Fitria Handayani; R.A. Supriyono (Berkala Akuntansi dan Keuangan Indonesia, 2018)
This study examines the effect of using environmental perspective in BSC and management communication as moderating variable in performance evaluation using BSC. The 2x2 between-subject laboratory experiment was carried out on 113 Master of Management and Master of Accounting students, Faculty of Economics and Business, Universitas Gadjah Mada. The results showed that the use of the environmental perspective in the BSC has not been able to provide an influence on performance evaluation based on the BSC. In addition, the use of management communication has not been able to increase the effect of the use of the environmental perspective as an additional perspective of the BSC in performance evaluation. However, the use of environmental perspective and a high level of management communication provide significant influence on the decision on the allocation of bonuses by the team of evaluators allocated to managers.